Occupational exposure to organic particles and combustion products during pregnancy and birth outcome in a nationwide cohort study in Sweden. Issue 8 (23rd May 2019) - Norlén, Filip; Gustavsson, Per; Wiebert, Pernilla; Rylander, Lars; Westgren, Magnus; Plato, Nils; Albin, Maria; Selander, Jenny
Abstract : Objective: To study if children of women exposed to organic particles and combustion products at work during pregnancy, have an increased risk of low birth weight, preterm birth or small for gestational age. Methods: A nationwide cohort of all occupationally active mothers and their children from single births during 1994 to the end of 2012 (1 182 138 observations) was formed. Information on birth outcome was obtained from the medical birth register. Information on absence from work, education, occupation, age, nationality and smoking habits was obtained from national registers. A job exposure matrix (FINJEM) was used to assess the exposure. Results: Pregnant women with low absence from work and high (>50th percentile) exposure to organic particles had an increased risk of giving birth to children with low birth weight (OR=1.19; 95% CI: 1.07 to 1.32), small for gestational age (OR=1.22; 95% CI: 1.07 to 1.38) or preterm birth (OR=1.17; 95% CI: 1.08 to 1.27). Subgroup analyses showed an increased risk of small for gestational age in association with exposure to oil mist. Exposure to oil mist and cooking fumes was associated with low birth weight. Paper and other organic dust was associated with preterm birth. Exposure to combustion products showed an increased risk of small for gestational age (OR=1.40; 95% CI: 1.15 to 1.71). Conclusions: The results indicate that occupational exposure to organic particles or combustion products during pregnancy is associated with restriction of fetal growth and preterm birth. More studies are needed to confirm a casual association.